Analysis of Factors Influencing In Purchasing Decision at Coffee Nest - Christin Natalia Sianipar; Nursaimatussaddiya; Lukieto Cahyadi (International Journal of Economics (IJEC), 2022)
In this study, a sample of 96 people was used which was taken from the coffee nest customer. This study tries to answer the research objective, namely to determine the factor analysis that influences the purchasing decision at the coffee nest customer at the coffee nest customer. Hypothesis Testing the Effect of Personal Factor Variable (X2 ) on the Purchase Decision Variable (Y). The calculated t value is 1,819 the t table value is (1.98580) From the description it can be seen that t count (1.819) < t table (1.98580), and the significance value is 0.072 > 0.05, it can be concluded that the Personal Factor variable (X2) has no effect on the Purchase Decision variable (Y). Hypothesis Testing the Effect of Psychological Factor Variables (X 3 ) on Purchase Decision Variables (Y). The value of t count is 5.796 , the value of t table is ( 1.98580 ). Hypothesis Testing the Effect of Social Factor Variables (X 1 ), Personal Factor Variables (X 2 ) and Psychological Factor Variables (X 3 ) on Purchase Decision Variables (Y). The calculated F value is 13,310 , the F table value is 2.70 . From this description, it can be seen that F arithmetic (13.310) > F table (2.70), and a significance value of 0.000 <0.05, it can be concluded that the Social Factor variable (X1), Personal Factor variable (X2) and Psychological Factor variable (X3) has a joint (simultaneous) effect on the Purchase Decision variable (Y).